Systemic features of retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations: a monogenic small vessel disease. (8th November 2018) - Pelzer, N.; Hoogeveen, E. S.; Haan, J.; Bunnik, R.; Poot, C. C.; van Zwet, E. W.; Inderson, A.; Fogteloo, A. J.; Reinders, M. E. J.; Middelkoop, H. A. M.; Kruit, M. C.; van den Maagdenberg, A. M. J. M.; et al.
Abstract: Background: Retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations (RVCL‐S) is a small vessel disease caused by C‐terminal truncating TREX1 mutations. The disease is typically characterized by vascular retinopathy and focal and global brain dysfunction. Systemic manifestations have also been reported but not yet systematically investigated. Methods: In a cross‐sectional study, we compared the clinical characteristics of 33 TREX1 mutation carriers (MC+) from three Dutch RVCL‐S families with those of 37 family members without TREX1 mutation (MC‐). All participants were investigated using personal interviews, questionnaires, physical, neurological and neuropsychological examinations, blood and urine tests, and brain MRI. Results: In MC+, vascular retinopathy and Raynaud's phenomenon were the earliest symptoms presenting from age 20 onwards. Kidney disease became manifest from around age 35, followed by liver disease, anaemia, markers of inflammation and, in some MC+, migraine and subclinical hypothyroidism, all from age 40. Cerebral deficits usually started mildly around age 50, associated with white matter and intracerebral mass lesions, and becoming severe around age 60–65. Conclusions: Retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations is a rare, but likely underdiagnosed, systemic small vessel disease typically starting with vascular retinopathy, followed by multiple internal organ disease, progressive brain dysfunction, and ultimately premature death.